SURGICAL EDUCATION AND TRAINING ADAPTATION IN RESPONSE TO THE COVID-19 PANDEMIC: A LITERATURE REVIEW - Rudiman, Reno; Hapsari, Putie (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: As a global health emergency, the COVID-19 pandemic has affected all medical education and training, including surgical specialities. The number of elective surgeries dropped significantly as both an impact of the pandemic and a way of limiting the spread of the disease. There was confusion about continuing surgical education and training at the beginning of the pandemic. However, as the pandemic continued, we adapted to the new conditions and regulations. Social distancing, testing, and quarantine were promoted. The study aimed to show how surgical education and training adapt to the COVID-19 pandemic worldwide and share how we do it in Indonesia.Methods: The authors gathered relevant literature from several publications sites, using the keywords “surgical education,” “surgical adaptation,” and “COVID-19.”Results: In order to decrease contacts, the number of people in the operating room was reduced, clinical rounds were cancelled, and face-to-face training and lectures were moved to online platforms, namely Zoom and Google Meet. The number of residents on clinical duties was decreased to limit the transmission. They are encouraged to study using different models by themselves to keep up with the required skills. They were required to learn and then be tested or reviewed by the supervisor. The use of simulation models and online learning platforms provided by several worldwide institutions has become popular.Conclusion: We learn that surgical education and training from the pandemic can develop into a more modern way of learning, consisting of a virtual learning strategy and simulation model. This hybrid learning of offline and online courses can aid the growth of not only the residents but also the experienced surgeon.